Ultrasonographic approaches for breeding soundness evaluation of high and low libido buffalo bulls - SINGH, KHUSHPREET; KUMAR, AJEET; HONPARKHE, M; DADARWAL, D (The Indian Journal of Animal Sciences, 2015)
The present study was conducted to evaluate ultrasound based rump fat thickness, testicular echogenecity and accessory sex glands diameter in relation to libido in breeding buffalo bulls. Breeding buffalo bulls (20) maintained at bull station of the university and Bhattian, Khanna were used in this study. Bulls were categorized into high (n=10) and low libido (n=10) on the basis of reaction time (high libido < 5 min; low libido > 5 min). Rump fat thickness, testicular echogenecity and diameter of prostate gland and seminal vesicles were measured using ultrasonography (5 MHz probe). The average rump fat thickness was significantly lower in high libido bulls (5.29±0.62 mm) as compared to low libido bulls (7.29±0.93 mm). The average diameter of seminal vesicles was significantly lower (1.54±0.05 cm) in high libido bulls as compared to low libido bulls (1.73±0.08 cm). Diameter of prostate gland was similar in both the groups. It was concluded that internal ultrasound based rump fat thickness and seminal vesicle diameter can be used to differentiate high libido buffalo bulls.